Peningkatan Mutu Layanan Pendidikan Melalui Kinerja Tenaga Kependidikan Berbasis Teknologi Informasi Dan Komunikasi, - Minnah Elwiddah (Proceedings of Annual Conference on Islamic Educational Management, 2021)
: This paper aims to describe the extent to which the performance of Information and Communication Technology-based education personnel in improving the quality of educational services plays a role. Information and communication technology, either directly or indirectly, has made a major contribution in realizing the improvement of the quality of education services. The roles of Information and Communication Technology in improving the quality of educational services are: (1) With the existence of Information and Communication Technology, the work of educational staff in educational institutions can be done on time, so that services can be more optimal, (2) Use of time more efficiently, and minimize mistakes and errors, (3) Information and Communication Technology-based school administration is very helpful in compiling dapodik data, and school archives, (4) Very helpful in filling out report cards (e-raport), (5) Very helpful for parents in terms of registering their children to school, because educational institutions have implemented online New Student Admission, so parents don’t have to bother coming to school because they can register online.